Penegakan Hukum Terhadap Perjudian Online Berdasarakan Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi Dan Transaksi Elektronik - Prasetya, Ahadi Fajrin; Rahayu, Astri (Universitas Sang Bumi Ruwa Jurai, 2023)
Gambling is a game where players bet using money to choose one option among several options where only one choice is correct and wins. Law enforcement against gambling is not optimal, gamblers and bookies are not punished according to applicable law, even though this gambling is clearly a criminal act that is against the law in Indonesia. The problems in this study are regarding Law Enforcement Based on Law Number 19 of 2016 Concerning Information and Electronic Transactions Against Online Gambling and What are the inhibiting factors in Law Enforcement Based on Law Number 19 of 2016 concerning Information and Electronic Transactions Against Online Gambling. This study uses Law enforcement theory from Lawrence Meir Friedman and Soerjono Soekanto's Inhibiting Factor Theory. The research method uses the type of empirical normative research. Research Results and Discussion: Law Enforcement Based on Law Number 19 of 2016 Concerning information and online gambling electronic transactions is to make preventive and repressive efforts. The inhibiting factors in law enforcement against online gambling are the legal factors themselves, human resource factors, facilities and community factors. The conclusions and suggestions in this study are that prevention efforts are needed by blocking sites that have gambling content as part of the government's efforts to eradicate online gambling crimes. Law enforcers should do more outreach to the public about the dangers of online gambling crimes.